Colonial Disaster, the “Capitalocene” and Contemporary Lessons: The Great Flood of 1924 in Southern India - Sudhindranath, Mahendranath; Lourdusamy, John Bosco (Blue Papers, 2026)
Floods impact many Sustainable Development Goals (SDGs) and aspects of sanitation and water supply. They are especially detrimental to those in lower socio-economic strata. The 2018 Kerala floods disrupted the lives of 5.4 million people, resulting in funds and attention being diverted from SDGs priorities and toward rebuilding and rehabilitation efforts. Such ravages of nature often result from the over-exploitation of local natural resources and the mismanagement of infrastructure. Colonialism was a watershed in such ecological destruction. The Great Flood of 1924, which devastated parts of present-day Kerala, is an example of a colonial-era-induced natural disaster. A century later, revisiting this disaster in the light of Kerala’s 2018 floods offers instructive pointers for achieving disaster resilience today – in a region known for its rich biodiversity and population density. This study also highlights how historical forces like colonialism contributed to transforming this once peripheral region into a “risk society.”